1998
DOI: 10.1021/jo971698a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of New 1,4-Bis(alkylthio)-3,6-diarylthieno[3,4-c]thiophene Derivatives

Abstract: 1,4-Bis(tert-butylthio)-3,6-diphenyl- and 3,6-di(2-thienyl)thieno[3,4-c]thiophenes (2a,b)were synthesized from 2-(tert-butylthio)-3-phenyl- and 3-(2-thienyl)cyclopropenethiones (1a,b) and triphenylphosphine in dry benzene at 50 degrees C, although similar treatment of 2,4,6-triisopropylphenyl, N,N-diethylamino, pyrrolidino, and diphenyl-substituted cyclopropenethiones (1c-h) did not result in the production of the corresponding thieno[3,4-c]thiophene derivatives. The possible reaction pathway for the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This is a new method to synthesize compound 3, which avoids the photochemical reaction conditions and bothersome purification steps that previous methods suffered from. 12,13 The target compounds 4 and 5 were obtained via Suzuki coupling reactions of 2 with a-thiopheneboronic acid in different ratios. Compound 6 was synthesized via an excess of tributyl(5-hexylthiophen-2-yl)stannane 14 with compound 2 to ensure completion of the Stillecoupling reaction in 75% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a new method to synthesize compound 3, which avoids the photochemical reaction conditions and bothersome purification steps that previous methods suffered from. 12,13 The target compounds 4 and 5 were obtained via Suzuki coupling reactions of 2 with a-thiopheneboronic acid in different ratios. Compound 6 was synthesized via an excess of tributyl(5-hexylthiophen-2-yl)stannane 14 with compound 2 to ensure completion of the Stillecoupling reaction in 75% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic data for 3: chemical formula: C 30 H 20 S 2 ; formula weight (M): 444.58; temperature: 293(2) K; monoclinic; P2 1 /c; a = 6.1134 (12) 14)1, g = 90.001; V = 709.8(3) Å 3 ; Z = 2; r calcd = 2.163 g cm À3 ; number of reflections collected: 1223; final R = 0.0971, wR = 0.2700. From the crystallographic data of compound 5, it is found that there is a large and unexplained residual electron density of 2.65 in this structure, located at (0.0656, 0.7156, 0.0961) and at a distance of 1.29 Å from the Br atoms.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…Computational studies on biradicaloids ( B ; E=CH 2 , NH, O and S; R=H) and beryllium analogues ( B ; E=Be; R=H) shed light on the theoretical stability and the singlet–triplet states of this class of compounds. In the synthesis of 1,3,4,6‐tetrakis( tert ‐butylthio)thieno[3,4‐ c ]thiophene, a dithiocyclooctatetraene ( B ; E=S, R= t Bu−S) was mentioned as an intermediate, which showed C−C coupling of the central allene carbon atoms . To our knowledge, the disilacyclooctatetraene (structure of type B , E=SiMe 2 , R=SiMe 3 ), which was described by Barton in 1993, using in situ ‐ generated Li 2 (Me 3 SiC 3 SiMe 3 ) ( 1 ) and Me 2 SiCl 2 , is the only example of this class of compounds that has been fully characterized and structurally investigated …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Previous work by Yoneda and Matsumura further revealed that triaryl phosphines can react with diphenyl CpS via nucleophilic addition to the alkene. 17,18 Based on this precedent, we surmised that CpS derivatives could react with substituted phosphines (similar to CpO probes), ultimately providing thiocarbonyl products (Figure 1A). Thiocarbonyls are widely used in fluorescence quenching and other biophysical experiments with proteins, 19,20 suggesting that they too are stable and biocompatible.…”
mentioning
confidence: 99%
“…CpS differs from cyclopropenone (CpO) by only a single atom and would thus likely be small enough to avoid perturbing target biomolecules or pathways. CpS is also known to participate in a variety of transformations, including photocleavage reactions , and ring-opening cycloadditions. , Previous work by Yoneda and Matsumura further revealed that triarylphosphines can react with diphenyl CpS via nucleophilic addition to the alkene. , Based on this precedent, we surmised that CpS derivatives could react with substituted phosphines (similar to CpO probes), ultimately providing thiocarbonyl products (Figure A). Thiocarbonyls are widely used in fluorescence quenching and other biophysical experiments with proteins, , suggesting that they too are stable and biocompatible. , Thioamides, in particular, are known to exhibit improved proteolytic stabilities and can increase peptide half-lives in biological media …”
mentioning
confidence: 99%